Antibiotics and antifungals in VLBW infants - Laura Cuzzolin (Hygeia Press di Corridori Marinella, 2015)
Very low birth weight infants are particularly vulnerable to bacterial and fungal infections. This leads to a common use of antiinfectives, often on a prophylactic basis. Due to the limited available information and the lack of guidelines, the use of antibacterials and antifungals in preterm newborns admitted to Neonatal Intensive Care Units is characterized by a large variability and these drugs are frequently given with different modalities, particularly as regards dosage and frequency, and in an off-label manner. This article provides an updated overview of the current situation on the use of antiinfectives in prematures, by reporting information derived by an analysis of the literature.   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)